Spectroscopic Evidence for an Additional Symmetry Breaking in the Nematic State of FeSe Superconductor - Cong Li (American Physical Society, 2020)
The iron-based superconductor FeSe has attracted much recent attention because of its simple crystal structure, distinct electronic structure, and rich physics exhibited by itself and its derivatives. Determination of its intrinsic electronic structure is crucial to understanding its physical properties and superconductivity mechanism. Both theoretical and experimental studies so far have provided a picture that FeSe consists of one holelike Fermi surface around the Brillouin zone center in its nematic state. Here we report direct observation of two holelike Fermi surface sheets around the Brillouin zone center, and the splitting of the associated bands, in the nematic state of FeSe by taking high-resolution laser-based angle-resolved photoemission measurements. These results indicate that, in addition to nematic order and spin-orbit coupling, there is an additional order in FeSe that breaks either inversion or time-reversal symmetries. The new Fermi surface topology asks for reexamination of the existing theoretical and experimental understanding of FeSe and stimulates further efforts to identify the origin of the hidden order in its nematic state.